Explanation and understanding in the human sciences - Mahajan, Gurpreet (New Delhi ; Oxford : Oxford University Press, 2011)
Gurpreet Mahajan surveys each of the major forms of inquiry - hermeneutic understanding, narrative, reason-action, and causal explanation - to examine how each method changes our perceptions of social reality. This edition includes a new Preface that discusses the evolution in social sciences over the last twenty years.
Previous ed.: 1997.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social sciences -- Methodology; Causation